2006
DOI: 10.1021/ja0604010
|View full text |Cite
|
Sign up to set email alerts
|

Methane Activation by Titanium Monoxide Molecules:  A Matrix Isolation Infrared Spectroscopic and Theoretical Study

Abstract: Reactions of titanium monoxides with methane have been investigated using matrix isolation infrared spectroscopy and theoretical calculations. Titanium derivatives of several simple oxyhydrocarbons have been prepared and identified. The titanium monoxide molecules prepared by laser evaporation of bulk TiO2 target reacted with methane to form the TiO(CH4) complex in solid argon, which was predicted to have C3v symmetry with the oxygen atom coordinated to one hydrogen atom of the methane molecule. The complex re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 82 publications
(81 reference statements)
2
63
0
2
Order By: Relevance
“…Werden isolierte Neutralatome (M = Fe, [70] Si, [71] B, [72] Be, [73] Mg, [73a] Sc, [74] Ti [75] oder Mn [70a] ) in einer Matrix durch thermische oder photochemische Anregung, kinetisch kontrolliert, mit Methanol zur Reaktion gebracht, dann erfolgt in den Begegnungskomplexen M(CH 3 OH) ausnahmslos die Aktivierung der stärkeren O-H-Bindung (Schema 4, Reaktionsweg A ) unter Bildung der jeweiligen [M]-OCH 3 -Spezies. [76] Wie nicht anders zu erwarten, verläuft die Methanoloxidation auf Sauerstoff-freien Oberflächen nach einem anderen Mechanismus.…”
Section: Der Erste Schritt: Spaltung Der Starken O-h-oder Der Schwächunclassified
“…Werden isolierte Neutralatome (M = Fe, [70] Si, [71] B, [72] Be, [73] Mg, [73a] Sc, [74] Ti [75] oder Mn [70a] ) in einer Matrix durch thermische oder photochemische Anregung, kinetisch kontrolliert, mit Methanol zur Reaktion gebracht, dann erfolgt in den Begegnungskomplexen M(CH 3 OH) ausnahmslos die Aktivierung der stärkeren O-H-Bindung (Schema 4, Reaktionsweg A ) unter Bildung der jeweiligen [M]-OCH 3 -Spezies. [76] Wie nicht anders zu erwarten, verläuft die Methanoloxidation auf Sauerstoff-freien Oberflächen nach einem anderen Mechanismus.…”
Section: Der Erste Schritt: Spaltung Der Starken O-h-oder Der Schwächunclassified
“…[31,32] They suggested that the trend in reactivity can be rationalized in terms of change in electrophilicity of MO x , the strength of the MAO bond, and the binding property of MO x to methyl or hydrogen as M and x are varied. [31,32] Zhou and coworkers [33][34][35][36][37] have investigated the MO þ CH 4 (M ¼ Fe, Mn, Nb, and Ta) and M þ CH 3 OH (M ¼ Sc, Ti, Mn, and Fe) model reactions, regarding the mechanism for the catalytic methane-to-methanol conversion process by quantum chemical calculations coupled with matrix isolation spectroscopy. For the late transition metals, Mn and Fe, the inserted CH 3 MOH is a critical intermediate in both MO þ CH 4 and M þ CH 3 OH reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For the late transition metals, Mn and Fe, the inserted CH 3 MOH is a critical intermediate in both MO þ CH 4 and M þ CH 3 OH reactions. [33][34][35][36][37] For the group IV and V transition metals, the inserted CH 3 OMH and CH 3 M(O)H are the crucial intermediates. [33][34][35][36][37] For Sc, CH 3 ScOH is an important intermediate in the…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18, 21 Zhou and coworkers have deliberately investigated the MO (M 5 Fe, Mn, Nb, Ta) 1 CH 4 and M (M 5 Sc, Ti, Mn, Fe) 1 CH 3 OH model reaction regarding the mechanism for the catalytic methane-to-methanol conversion process by quantum chemical calculations coupled with matrix isolation spectroscopy. 15,[37][38][39][40] It is proposed that for the late transition metals, Mn and Fe, the inserted CH 3 MOH molecule is a critical intermediate in both MO 1 CH 4 and M 1 CH 3 OH reactions; while for the group IV and V transition metals, the inserted CH 3 OMH and CH 3 M(O)H molecules are the crucial intermediates; and for Sc, the CH 3 ScOH molecule is an important intermediate in the ScO 1 CH 4 reaction, whereas the CH 3 OScH is a critical intermediate in the Sc 1 CH 3 OH reaction. 15,[37][38][39][40] Previously, we have reported the gas-phase reaction mechanism of CH 4 with MO (M 5 Mg, Ca, Sr), and put forward that the reaction may proceed via two kinds of important reaction intermediates, HOMCH 3 and HMOCH 3 , and the hydroxy intermediate HOMCH 3 is more preferable than the methoxy intermediate HMOCH 3 , while the products, MOH 1 CH 3 , are more favorable than M 1 CH 3 OH.…”
Section: Introductionmentioning
confidence: 99%